The role of the NADPH oxidase derived brain oxidative stress in the cocaine-related death associated with excited delirium: A literature review. (6th September 2016) - Schiavone, Stefania; Neri, Margherita; Mhillaj, Emanuela; Pomara, Cristoforo; Trabace, Luigia; Turillazzi, Emanuela
Highlights: Excited Delirium Syndrome is commonly associated to cocaine abuse. The pathophysiology of this syndrome is complex and not yet fully understood. Increased reactive oxygen species production by the NADPH oxidase NOX enzymes might play a crucial role. Data from animal models and human evidence are discussed in this review. Abstract: Excited delirium syndrome (ExDS) is a term used to describe a clinical condition characterized by bizarre and aggressive behaviour, commonly associated with the use of psychoactive compounds, especially cocaine. The pathophysiology of ExDS is complex and not yet fully understood. In addition to a central dopamine hypothesis, other mechanisms are thought to be involved in cocaine-related ExDS, such as increased reactive oxygen species production by the family of the NADPH oxidase NOX enzymes. In this review, we will summarize current knowledge on the crucial contribution of brain NADPH oxidase derived oxidative stress in the development of cocaine-induced ExDS. Data from animal models as well as human evidence will be discussed.